2020
DOI: 10.1088/1361-6560/abbf98
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solid tank design for fan-beam optical CT based 3D radiation dosimetry

Abstract: Optical computed tomography (CT) is one of the leading modalities for imaging gel dosimeters for 3D radiation dosimetry. There exist multiple scanner designs that have showcased excellent 3D dose verification capabilities of optical CT gel dosimetry. However, due to multiple experimental and reconstruction based factors there is currently no single scanner that has become a preferred standard. A significant challenge with setup and maintenance can be attributed to maintaining a large refractive index bath (1–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…We acknowledge that the system matrices used for this experiment are standard parallel‐beam and fan‐beam systems and do not incorporate the refraction properties present in optical CT. The current optical CT system being used by our research group is still in development 32 and hence no accurate system matrices were available. Nonetheless, this work presents a valuable step in working towards the goal of designing an effective optical CT system for radiotherapy dose verification.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the system matrices used for this experiment are standard parallel‐beam and fan‐beam systems and do not incorporate the refraction properties present in optical CT. The current optical CT system being used by our research group is still in development 32 and hence no accurate system matrices were available. Nonetheless, this work presents a valuable step in working towards the goal of designing an effective optical CT system for radiotherapy dose verification.…”
Section: Discussionmentioning
confidence: 99%
“…An in-house ray tracing simulator has been developed to track the path of each ray as it traverses the different mediums of the prototype tabletop solid-tank fan-beam optical CT scanner developed at the University of British Columbia -Okanagan (Figure1) [8]. The scanner consists of an acrylic (PMMA) block with a curved face and a hole bored through it in which a cylindrical radiochromic gel dosimeter is inserted.…”
Section: Methodsmentioning
confidence: 99%
“…Figure1. Ray tracing simulator produced visual representation of primary (green) and crossover (red) raypaths through the prototype optical CT system of[8].…”
mentioning
confidence: 99%
“…The rationale behind the design, as well as the procedure have been discussed in-depth in a previously published paper [12]. The prototype fan-beam scanner features a 635nm laser diode with a 60° linegenerating Powell lens.…”
Section: Methodsmentioning
confidence: 99%
“…Previously published work has demonstrated that a solid tank scanner with a severely reduced need for index matching can be built and optimized given a set of design criteria [12]. The purpose of this work is to commission the design found from that previous research.…”
Section: Introductionmentioning
confidence: 99%